The Effect Of Integrating Stempreneur 6E Project-Based Module In Enhancing Lower Secondary School Students’ Entrepreneurial Thinking - Hashim, Hartini (2022)
The purpose of this study was to analyse the impact of STEMPRENEUR MODULE on the entrepreneurial mind of lower secondary students. Five theories were involved in this study; Theory of Constructvisme, Theory of Resilience, Vgotsky’s Social Constructive Theory, Bruner’s Cognitive, and Kolb’s Theory. However, Theory of Constructivisme would be the umbrella for the others four theories. This research was conducted with a pre-experiment, where a one group pre-test, post-test, and post-test II design was applied. A total of 44 Form-One students from one of the secondary schools in Kota Bharu, Kelantan participated in the study, which involved outdoor activities and after-school programmes, conducted with their parents' permission. The data was collected three times, during the pre-test, post-test and post-test 2, from the distributed questionnaires; Entrepreneurial Mind. Besides, students' interviews, analysed photos and reflective journals were also used as supporting quantitative data. The findings of MANOVA revealed that, STEMPRENEUR Module brings a positive effect on students’ entrepreneurial minds. The study also found that, a student’s entrepreneurial mind can be developed, and its inculcation should start at a very early stage, namely from the primary school level.